CONSTITUTIONALISM IN DEMOCRATIC SOUTH AFRICA: CELEBRATIONS, CONTESTATIONS AND CHALLENGES (The Strategic Review for Southern Africa, 2020)
South Africans often proudly proclaim that our Constitution is one of the most progressive in the world. Yet if you ask most South Africans how they really feel about gay rights, abortion and the death penalty, their answers, more often than not, contradict the values enshrined in the Constitution. (Ahmed 2014) This is the sobering assessment of the Chief Executive of the South African Human Rights Commission 20 years into democratic South Africa. The document adopted by The Constitution of the Republic of South Africa Act 108 of 1996 was considered an exemplary showpiece for the new democratic, human rights based era — embraced as "proudly South African" among the world's most enlightened legal frameworks. Taking stock almost two decades later, however, constitutionality seems to have not yet been deeply and firmly anchored in public awareness or ingrained into a ] social fabric guiding the fundamental values, ethics and norms as reflected by ordinary public perception and opinion. Nor have policy makers in the government seemingly internalised an unconditional respect for and recognition of the governance principles enshrined in this Constitution, as some recent examples seem to suggest. The current controversy around the "spy tapes", but even more so the contested role of the public protector — dubbed "a jewel in South Africa's constitutional crown" (Pieters 2014) — and her stance with regard to Nkandla and the obligations of the head of state to respond to her recommendations are obvious tips of the iceberg. But current discourses at the same time are a mirror image of the ongoing struggles over the power of definition and the interpretation, as well as adherence, to the rules of the game as laid down in the normative framework. As constitutions elsewhere, there is a discrepancy between what is stated, how it ought to be understood and interpreted, how it should be adhered to and applied, and what the intended effects, as well as the real consequences are. It therefore is not by accident that debates and contestations over the meaning and implications of constitutional principles are an eminently political affair and an integral part of governance. It would be more worrying, if this would not be the case, since this would suggest that those in control over society reign supreme in the sense of governing without checks and balances. So then let's have a closer look at the issues at stake.